2006
DOI: 10.1055/s-2004-834757
|View full text |Cite
|
Sign up to set email alerts
|

Prädiktoren für den psychopathologischen Entlassungsbefund bei akutpsychiatrischer, tagesklinischer und vollstationärer Behandlung

Abstract: Given the explorative character of the present study, further prospective studies are needed in order to cross-validate findings on the potential criteria for allocating acute mentally ill either to day-hospital or inpatient treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 3 publications
1
1
0
Order By: Relevance
“…Our study showed a significant relationship between the level of depressive symptoms ad admission and therapy outcome. This is in accordance with other studies also showing a higher benefit for depressed patients (2, 10, 21, 22).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our study showed a significant relationship between the level of depressive symptoms ad admission and therapy outcome. This is in accordance with other studies also showing a higher benefit for depressed patients (2, 10, 21, 22).…”
Section: Discussionsupporting
confidence: 93%
“…A number of studies have shown that patients who are depressed are significantly more likely to benefit from inpatient psychotherapy (2, 10, 21, 22). Patients with depressive disorder showed better therapy success than patients with other non-somatic diseases (6).…”
Section: Introductionmentioning
confidence: 99%